STRUKTUR KOMUNITAS MAKROZOOBENTOS SEBAGAI INDIKATOR PERUBAHAN KUALITAS PERAIRAN DI SUNGAI BELAWAN KECAMATAN PANCUR BATU KABUPATEN DELI SERDANG - Nurul Fadillah; Pindi Patana; Maragunung Dalimunthe (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2016)
Activities in Belawan River has caused water quality degradation, such asecological conditions of biota particularly macrozoobenthos. This research aimedto know the community structure of macrozoobenthos and water quality based onDiversity Index and Abundance and Biomass Comparison (ABC) curve. Thisresearch was conducted in Belawan River Pancur Batu sub district Deli Serdangregency from April until June 2015. The sampling was done by purposive randomsampling method at three stations for three weeks. Results of this research found 9species of macrozoobenthos divided into 6 family and 2 classes, those wereGastropods and Insecta. The density was ranged from 4.33 to 45.0 ind /m2, whilediversity index 1.29 to 1.51 with medium level of diversity rate. Evenness indexwas ranged from 0.72 to 0.78 and dominance index was ranged from 0.24 to 0.25.The water quality of Belawan River was divided into two categories, based on thediversity index was medium polluted category and based on ABC curve was notpolluted – medium polluted categories.Keywords: Macrozoobenthos, Community Structure, Diversity Index, ABC Curve,Pollution Levels